Vacancies mediated ordering in Ni-Mn-Ga shape memory alloys. (1st July 2022) - Mérida, D.; Unzueta, I.; Sánchez-Alarcos, V.; Recarte, V.; Pérez-Landazábal, J.I.; García, J.A.; Plazaola, F.
Graphical abstract: Abstract: Vacancy mediated diffusion is the main atomic mechanism that controls the ordering of substitutional alloys. In particular, in Ni-Mn-Ga shape memory alloys vacancies control the evolution of the L 2 1 atomic order degree and consequently most of the order-dependent properties of the martensitic transformation. This work adapts a general phenomenological model to quantify the evolution of the vacancy concentration during the ordering process for three different Ni-Mn-Ga alloys. The results show that out of equilibrium vacancies are responsible of the ordering process, fixing the set of parameters governing it. The present work shows the suitability of the model to determine the vacancy dynamics throughout any process in which they intervene.